The Principal's Strategy Based on the Noble Values of the Huma Betang Philosophy in Improving Teacher Performance at Palangka 2 Public Elementary School - Carolina Fransiska; Melinda Prawati; Widya Permata Dilla; Simpun Simpun; Femmy Femmy; Kristiani Natalia; Laila Rahmawati; Maneka Ciciana; Noorlaila Noorlaila; Bambang Eko Irawan (IKIP PGRI Bojonegoro, 2026)
The purpose of this research is to determine